A multigenerational pedigree of late-onset Alzheimer’s disease implies new genetic causes (2005)
ABSTRACT: We describe the clinical phenotype and pathology of a new autosomal dominant late-onset familial form of Alzheimer’s disease in four extensive kindred originated in a genetically isolated population. Twelve affected and 16 unaffected members of these kindred were examined clinically, and a brain post-mortem study was carried out in one case. The preliminary genetic assessment included complex segregation analysis, evaluation of the power to detect linkage, and exclusion of candidate genes. Dementia has been recorded for six generations in ancestors of examined cases. Review of death certificates allowed linking of all subjects in four extensive pedigrees. Affected individuals examined had progressive memory loss with onset between 57 and 74 years of age, along with seizures, myoclonus and parkinsonism in advanced stages. The brain of the case examined post- mortem showed widespread neocortical neuritic plaques and neurofibrillary tangles (stage VI of Braak), amyloid angiopathy, and Lewy bodies restricted to limbic areas. Sequencing exons 16 and 17 of amyloid precursor protein, and exons 4–12 of presenilin 1 and presenilin 2 genes did not disclose any mutations. Genotyping with markers D21S265, D14S71, D14S77, D1S2850 and D1S479 located 1–3 cM from the previously reported genes further excluded linkage to these genes. Seven out of 12 cases were apolipoprotein E (APOE) «3/3, although the presence of an APOE «4 allele was associated with an increased risk of dementia (odd ratio 6.17; 95% confidence interval: 1.15–33.15), but not to an earlier age of onset. Complex segregation analysis showed that the best model fitting the data was that of a major gene (dominant) with a gene frequency close to 3% in this population. Simulation analysis predicted an average logarithm of odds (LOD) of 2.2 at u = 0.05. These four families, which seem to be part of a common extended pedigree originated by a founder arriving in this region in the 18th century, represent an autosomal dominant late-onset familial Alzheimer’s disease not linked to previously known genetic loci. The simulation analysis suggests that it will be feasible to locate a novel responsible gene in these kindred.